Peran Perguruan Tinggi Agama Islam Dalam Mendorong Perkembangan Pendidikan Islam Di Indonesia - Hayatun Nisa; Alya, Alya; Idrus L (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the strategic role of Islamic Higher Education Institutions in advancing Islamic education in Indonesia through a non-empirical, descriptive-analytical library research design. Drawing on an integrative framework that combines historical, sociological, and pedagogical perspectives, the study synthesizes contemporary scholarly literature and policy documents to analyze institutional transformation, academic innovation, and socio-cultural contributions. The findings indicate that institutional transformation enhances governance structures and academic quality, enabling adaptive and competitive educational systems. Curriculum integration between Islamic sciences, general knowledge, and digital literacy fosters interdisciplinary competence and contextual learning relevant to global challenges. Furthermore, the socio-cultural role of these institutions contributes to strengthening religious moderation, civic responsibility, and ethical character formation, positioning them as agents of social transformation. The analysis highlights that the sustainability of Islamic education development depends on the alignment between institutional capacity, curriculum innovation, and societal engagement.